Antecedents and Consequences of Peer Support - Purbudi Wahyuni (AIBPM Publisher, 2022)
This article aims to build an understanding of antecedents and the consequences of peer support. This research examined 42 articles that analyze peer support consisting of nine journals that analyze concept, comments, and descriptive reviews, and 42 articles are analyzed empirically.. The findings show that individual perception is related to willingness to perform peer support. Peer support occurs when the relationship between others is based on belief, trust, attitude and interpersonal relationship mutually maintained.Â Â